Community Policing : Misnomer or Fact? - Mishra, Veerendra (India Sage Publications India Pvt. Ltd., 2011)
The interactions between police and the public has long been a forum for debate, particularly in recent times. Community Policing is a discussion of the underlying schools of though of "community policing", where these two different worlds meet.
Include Index and Illustrations
Keywords: Community policing -- India -- Police-community relations